Analisis Sentimen Terhadap Presidensi G20 2022 pada Media Sosial Twitter Menggunakan Metode Naïve Bayes - I Gusti Agung Indrawan; Dewa Ayu Indah Cahya Dewi; Ida Ayu Putu Ananda Wisdantini (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Twitter is one of the social media as a suitable forum to express opinions from the community today. Many people express their opinions through posts on social media Twitter on issues that are trending topics. One of the trending topics in 2022 is the implementation of the G20 presidency held in Bali, Indonesia. This issue, can generate positive or negative opinions from the community. In the research, a sentiment analysis will be carried out on the implementation of G20 presidency activities in 2022 using Python Google Colab, RapidMiner Studio, and Orange Data Mining. In the initial data collection, there are 24,840 data that will go through the stages of text pre-processing, labeling, sharing, and data classification using the Naïve Bayes classification method. So that it obtained the results of the classification of positive sentiment 1,600 data (72.37%) and negative sentiment 611 data (27.63%). Based on the results of the sentiment classification, it can be concluded that the public supports the implementation of G20 activities in 2022 in Bali, Indonesia, seen from positive sentiment more than negative sentiment. The Naïve Bayes classification has a fairly good performance in classifying the topics studied, where an accuracy value of 88.01% is obtained.